The Conscientisation and Politicisation of Maori Women - Nepe, Tuki (Te Pua, 1992)
Keywords: colonisation; decolonisation; discrimination; economic inequality; inequality; intersectionality; mana wāhine; periodicals; sexism; wāhine māori

Kia Tawharautia Te Matauranga Maori: Decolonising the Intellectual Property Regime in Aotearoa New Zealand - Kapa-Kingi, Eru (Victoria University of Wellington Law Review, 2020)
Gale Academic OneFile includes KIA TAWHARAUTIA TE MATAURANGA MAORI: DECOLONISING THE I by Eru Kapa-Kingi. Click to explore.
Keywords: decolonisation; intellectual property; mātauranga māori; tikanga | indigenous law; tino rangatiratanga; waitangi tribunal

Chapter 5: Where to next? Decolonisation and the stories in the land: Imagining Decolonisation - Jackson, Moana (Imagining Decolonisation, 2020)
Keywords: colonisation; decolonisation; hapū politics; iwi politics; rangatiritanga; tikanga | indigenous law

“Maori sovereignty” Donna Awatere 1982 - Kamau, Laura-Margaret Ngahere Te Pohe (2010)
This thesis explores the ambivalent nature of Maori political theory as expressed through the writings of Donna Awatere in her publication Maori Sovereignty. Consequently it traces the intellectual history of Maori political thought with a particular emphasis on how Maori have traditionally perceived and advanced their ‘sovereignty’ and its equivalent term, ‘tino rangatiratanga’. The reason for this emphasis is to show how Awatere changed Maori perception of their tino rangatiratanga when she coined the phrase ‘Maori Sovereignty’ in 1982. This work offers an insider’s account into New Zealand’s ‘movements of unity’ that had occurred during the 1970’s and 1980’s based on Awatere’s personal experiences and involvement in various groups. Further it sets out to capture the influences and events that led Awatere to write Maori Sovereignty in order to demonstrate how she had advanced Maori understanding of their tino rangatiratanga. In addition, its attempts to broaden Maori understanding of their tino rangatiratanga by analysing Awatere’s political theory in juxtaposition with global trends, more specifically, the decolonisation and nationalistic processes that occurred in the decades following World War Two. This thesis argues that Maori Sovereignty differed greatly from any other work previously written by both Maori and Pakeha as it challenged existing interpretations of how Maori had perceived and had advanced their tino rangatiratanga. Subsequently, Maori Sovereignty has carved its place as one of New Zealand’s most debated and misunderstood publication to ever come out of the 1980’s and because of this, the lack of proper analysis has given cause for this thesis.
Keywords: activism; decolonisation; land; land return; tino rangatiratanga; urbanisation

'Riria te riri, mahia te mahi’: The Politics and Development of Modern Māori Activism, 1968-78 - McDowell, Tiopira (ResearchSpace@Auckland, 2007)
This study discusses the origins, development and outcomes of the first wave of radical Māori activism between 1968 and 1978. It charts the events of the period and the body of politics, philosophies and strategies employed by Māori activists. It contends that the discipline of history as currently practised becomes problematic when it is applied to the study of non-western cultures, and that scholars undertaking research into Māori histories and communities need to develop a model or metaphor for writing history which is sympathetic to Māori epistemologies and priorities. To this end the text focuses primarily on the words and actions of the activists themselves in order to better understand the way activists conceptualized their world. Activists’ ideas and politics should not just be studied in a ‘race relations model’, that is, in terms of their impact on society and the Pākehā public, and the reaction of the government. Taking activism out of the race relations model and examining it on its own terms throws the movement’s concerns, subtleties and contradictions into sharper relief and provides a deeper understanding of its significance. The thesis is centrally concerned with how activists defined themselves, their actions and their politics, and will argue that Māori activism was implicated in the era’s emerging politics of identity. Māori activism was as much about reforming Māori and Pākehā attitudes towards Māori culture, society and identity as it was about policy and legislative reform. Furthermore, the thesis attempts to explain the influence on, and contribution to, the activist movement of three interrelated contexts: te Ao Māori, the Māori world, Aotearoa, national events, and te Ao Hurihuri, the international setting. It also pays special attention to the gender politics of the era. The work is divided into four chapters. The first covers the Māori world and the ‘big three’ issues of Māori activism: the Treaty of Waitangi, land loss and cultural alienation. The second chapter discusses the national context and the ‘big three’ issues of national politics during the era: apartheid sport, the Vietnam War and class politics. The third chapter deals with the international framework and the influence of global trends on local events, while the fourth chapter details the emergence of the Black women’s movement.
Keywords: activism; decolonisation; mana motuhake; protest; tiriti o waitangi/treaty of waitangi

Unearthing (de)colonial legal relations: Mining law in Aotearoa New Zealand - Bargh, Maria; Wagner, Estair Van (Decolonizing law: Indigenous, third world and settler perspectives, 2021)
Keywords: colonisation; crown policy; decolonisation; environment; tiriti o waitangi/treaty of waitangi

A Seat At The Table - Winter, Christine J. (Borderlands Journal, 2021)
Abstract Aotearoa New Zealand acknowledges mātauranga Māori in the two Acts and one Memorandum of Understanding recognising the ‘personhood’ status of three geographical regions—Te Awa Tupua, Te Urewera and Taranaki Maunga. They blend the legal fiction of corporate personhood with the already always understanding of human-nonhuman kinship and entanglement of M!ori philosophy, Māori knowledge and wisdom, and Māori epistemology. Through kaitiaki (trustees) these three entities have volition in their ongoing maintenance, development negotiations, and ‘land-use’, and ‘the rights, powers, duties and liabilities of a legal person’. These attributes suggest something more than mere volition in self-management and protection: they suggest agency. This article explores the implications of nonhuman agency as potential for political voice. As representatives of entanglement for all being—animal (including human), vegetable and elemental—and as a matter of justice they are, perhaps, obliged to participate in democracy and the nation is, perhaps, obliged to give them a ‘seat at the table’. As political agents with equal status to human and corporate persons Te Awa Tupua, Te Urewera and Taranaki Maunga might unsettle settler politics and challenge the imbalances of the Anthropocene.
Keywords: decolonisation; democracy

Decolonising Dignity for Inclusive Democracy - Winter, Christine J. (Environmental Values, 2019)
Gale Academic OneFile includes Decolonising Dignity for Inclusive Democracy by Christine J. Winter. Click to explore.
Keywords: decolonisation; dignity; environment; mana party; mauri; tapu

Decolonisation starts in a name: Moving on from the colonial pretence that 'Maori' or 'indigenous peoples' are explanatory frames - MacDonald, Lindsey Te Ata o Tu (Political Science, 2016)
This article examines why and how scholars should acknowledge and name each of the diverse political actors and institutions that typically are objectified as ‘indigenous peoples’ on the global stage, or ‘Māori’ in New Zealand. For instance, rather than suggesting a political relationship or conflict exists between ‘Māori and the Crown’, political scientists and theorists should name the political actors and political institutions for which Māori is a shorthand, for example, ‘Te Runanga o Ngai Tahu (the corporate entity of the Ngai Tahu whanui) and the Committee of Tuahiwi Marae disagreed with the Crown’. A variety of reasons are discussed as to why this objectification of Māori (and any other indigenous population) as a single political actor has occurred, the problems are pointed out, and a range of examples are given. Not every use of the terms ‘Māori’, ‘indigenous peoples’ or similar descriptors in political science stands in for a specific political actor (e.g. sometimes, it is suggesting a cleavage or a group at whom a policy is directed), but where scholars are describing or suggesting political action, they should be careful in their use of ethnic labels. I suggest that it would be more productive to study the specific contexts, intentions and actions of individuals and institutions that might consider indigeneity as being part of their identity.
Keywords: decolonisation; mana wāhine; self-determination

Decolonizing politics with insights from Indigenous Studies - Bargh, Maria (Identities, 2022)
Keywords: colonisation; decolonisation; education; mātauranga māori; rangatiratanga; tikanga | indigenous law